Sosialisasi Keamanan, Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) - Suherman Jaksa; Hardiansyah; Ervani Sultoni; Suhartono (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Management of Hazardous and Toxic Waste (B3) in Indonesia still faces various challenges, especially in the aspects of education and outreach which are not yet evenly distributed and effective. This service activity aims to assess the effectiveness of educational programs in increasing the understanding and compliance of the community and workers with B3 waste management procedures. Using a qualitative approach, data was obtained through pre-test and post-test, observation of socialization participants from various sectors. The results of service activities show that participatory and contextual-based training methods, such as Focus Group Discussions (FGD) and field simulations, are able to increase participants' knowledge and compliance significantly. However, the success of the program is highly dependent on the availability of resources, appropriate educational media, and cross-sector involvement. Therefore, the government and related agencies are advised to develop sustainable education programs that are adapted to the literacy level of participants and the local context, in order to strengthen the B3 waste management system that is oriented towards protecting health and the environment.